Panoramic Features of a Stafne Bone Defect Mimicking a Residual Cyst in an Edentulous Mandible - Putri Marina Sukmadewi; Riki Kristanto; Kadek Asri Asmita Pradnyana Putri (Indonesian Journal of Dentistry, 2026)
Background: Stafne bone defect is an uncommon, well-defined lingual cortical depression of the mandible, most often discovered incidentally as a unilocular radiolucency in the posterior region, and is regarded as a benign developmental anomaly related to soft-tissue inclusion, particularly salivary glands. Classic lesions typically occur below the inferior alveolar canal in middle-aged male patients, are asymptomatic, and do not require surgical treatment; however, anterior variants located in the premolar region are rare and frequently mimic odontogenic cysts on panoramic radiographs.Objective: The purpose of this case report is to highlight the diagnostic challenge of an anterior variant of Stafne bone defect and demonstrate the importance of advanced imaging in differentiating it from odontogenic lesions to avoid unnecessary surgery.Case: A 60-year-old edentulous male patient underwent panoramic radiography as part of a pre-prosthetic evaluation. The image revealed a well-defined radiolucent area in the edentulous mandible, leading to a provisional diagnosis of a residual cyst.Outcome: Further evaluation with Cone Beam Computed Tomography (CBCT) was performed. The three-dimensional images revealed a well-circumscribed lingual cortical depression in continuity with the mandibular cortex. There was no evidence of buccolingual expansion, root resorption, or features of an intraosseous cystic cavity. These imaging characteristics confirmed that the radiolucency represented a static bone concavity rather than a space-occupying lesion..Conclusion: The lesion's location and specific imaging characteristics were consistent with a Stafne bone defect. The use of CBCT was definitive in excluding a residual cyst, thereby preventing an unnecessary surgical intervention and confirming the benign, static nature of the defect